2007
DOI: 10.4049/jimmunol.179.2.1198
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-Mediated Neurotoxicity Is Inhibited by Morphine through an Opioid Receptor-Independent Reduction of NADPH Oxidase Activity

Abstract: Recent studies have shown that morphine modulates the function of glia cells through both opioid receptor dependent and independent mechanisms. However, the mechanism by which morphine regulates neuronal disorders through the alteration of microglia activity remains unclear. In this study, using rat primary mesencephalic neuron-glia cultures, we report that both l-morphine and its synthetic stereoenantiomer, d-morphine, an ineffective opioid receptor agonist, significantly reduced LPS- or 1-methyl-4-phenylpyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 60 publications
4
67
0
Order By: Relevance
“…Our work has demonstrated that the (ϩ)-isomers of morphine and methadone are capable of inducing allodynia and hyperalgesia accompanied by expression of spinal proinflammatory cytokines (Hutchinson et al, 2010a). (ϩ)-Morphine has also been demonstrated to induce hyper-responsivity when injected in the periaqueductal gray area (Jacquet et al, 1977), to bind nonstereoselectively to mouse thymocytes and a macrophage cell line (Roy et al, 1991(Roy et al, , 1992(Roy et al, , 1996, and, surprisingly, to protect dopamine neurons from toxicity (Qian et al, 2007). These later neuroprotective actions of (ϩ)-morphine at first seem contrary to the hypothesized detrimental effects of inducing a proinflammatory central immune NEUROIMMUNOPHARMACOLOGIC IMPLICATIONS FOR OPIOID ANALGESIA signal.…”
Section: The Clinical Predicament Of Ineffective Opioid Analgesia Andmentioning
confidence: 99%
“…Our work has demonstrated that the (ϩ)-isomers of morphine and methadone are capable of inducing allodynia and hyperalgesia accompanied by expression of spinal proinflammatory cytokines (Hutchinson et al, 2010a). (ϩ)-Morphine has also been demonstrated to induce hyper-responsivity when injected in the periaqueductal gray area (Jacquet et al, 1977), to bind nonstereoselectively to mouse thymocytes and a macrophage cell line (Roy et al, 1991(Roy et al, , 1992(Roy et al, , 1996, and, surprisingly, to protect dopamine neurons from toxicity (Qian et al, 2007). These later neuroprotective actions of (ϩ)-morphine at first seem contrary to the hypothesized detrimental effects of inducing a proinflammatory central immune NEUROIMMUNOPHARMACOLOGIC IMPLICATIONS FOR OPIOID ANALGESIA signal.…”
Section: The Clinical Predicament Of Ineffective Opioid Analgesia Andmentioning
confidence: 99%
“…The mu-opioid receptors increase migration and upregulate expression of P2X 4 purinoceptors in cultured rat microglia (388). On the contrary, in neuronal-glial cultures prepared from rat mesencephalon, morphine significantly reduced microglial neurotoxicity and LPS-induced microglial activation, albeit through an unknown pathway that, most likely, did not involve opioid receptors (737). Reportedly morphine can also cooperate with HIV-1 transactivating protein Tat in stimulating microglial activation and secretion of proinflammatory factors (76).…”
Section: Opioid Receptorsmentioning
confidence: 99%
“…In zebrafish embryos, morphine, at certain concentrations, enhances neuron proliferation, increases the number of certain neuronal populations, and protects against glutamate damage in motor neurons and Pax-6-positive neurons in vivo (Sanchez-Simon et al, 2010). Morphine is found to be protective against microglia-mediated lipopolysccharide-or 1-methyl-4-phenylpyridinium-induced dopaminergic neurotoxicity in rat primary mesencephalic neuron/glia cultures (Qian et al, 2007). In rat neuronal/glial cultures, morphine is reported to prevent cell death induced by HIV envelope glycoprotein gp120IIIB or BaL (Avdoshina et al, 2010).…”
Section: Introductionmentioning
confidence: 99%